2011
DOI: 10.1093/humrep/deq378
|View full text |Cite
|
Sign up to set email alerts
|

Acute increase in plasma D-dimer level in ovarian torsion: an experimental study

Abstract: If the observations made in a rat model are extended to humans, plasma D-dimer measurement may be a valuable parameter in the early diagnosis of ovarian torsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…Serum D-dimer, ischemia-modified albumin, IL-6, IL-8, TNF-a, and E-selectin, have been investigated as serum markers in patients with ovarian torsion. Among these, elevated IL-6, D-dimer, and ischemia-modified albumin concentrations have been shown to be associated with ovarian torsion [2,[11][12][13][14][15]. Kart et al investigated the diagnostic value of plasma D-dimer level in an experimental rat ovarian torsion model and stated that D-dimer was well correlated with histopathological damage scores of ovarian injury and might be used as a plasma marker in early detection of ovarian torsion [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum D-dimer, ischemia-modified albumin, IL-6, IL-8, TNF-a, and E-selectin, have been investigated as serum markers in patients with ovarian torsion. Among these, elevated IL-6, D-dimer, and ischemia-modified albumin concentrations have been shown to be associated with ovarian torsion [2,[11][12][13][14][15]. Kart et al investigated the diagnostic value of plasma D-dimer level in an experimental rat ovarian torsion model and stated that D-dimer was well correlated with histopathological damage scores of ovarian injury and might be used as a plasma marker in early detection of ovarian torsion [14].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, elevated IL-6, D-dimer, and ischemia-modified albumin concentrations have been shown to be associated with ovarian torsion [2,[11][12][13][14][15]. Kart et al investigated the diagnostic value of plasma D-dimer level in an experimental rat ovarian torsion model and stated that D-dimer was well correlated with histopathological damage scores of ovarian injury and might be used as a plasma marker in early detection of ovarian torsion [14]. Aran et al studied ischemia-modified albumin levels in a rat model and concluded that it was a useful adjunct that could be used in the diagnosis of ovarian torsion and also stated that ischemia-modified albumin levels were correlated with the semiquantitative histologic scores of the specimens [15].…”
Section: Discussionmentioning
confidence: 99%
“…The detorsion group had the highest score for four ovarian injury parameters. Previous studies using a cellular scoring system have reported more ovarian damage after detorsion than due to the torsion [24,25]. Ischemia, which causes insufficient blood flow and insufficient oxygen support, leads to a decrease in the production of ATP, an increase in the production of lactic acid, and the accumulation of lipid peroxidase in tissue [5].…”
Section: Discussionmentioning
confidence: 99%
“…The only serum marker test studied in human subjects is interleukin (IL)-6, which was found to be elevated in ovarian torsion [3]. In our previous experimental studies (in animals), we also showed that serum ischemia-modified albumin (IMA) and D -dimer may be used in the early diagnosis of ovarian torsion [4,5]. Since these studies were experimental, the role of IMA in the diagnosis of ovarian torsion in humans and the threshold value of IMA have not been known or previously reported.…”
Section: Introductionmentioning
confidence: 99%